(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
استهدفت الدراسة التعرف على بعض الخصائص الاجتماعية والثقافية لدى مربي الإبل كالوضع الاجتماعي والتعليم وعادات الزواج والأنشطة الملقاة على عاتق المرأة في تلك المجتمعات. والتعرف على بعض الممارسات الفنية كآلية تشكيل قطيع الإبل، وممارسات تقديم الأعلاف، والطرق المتبعة في لمعالجة قطيع الإبل من الأمراض. ولتحقيق أهداف الدراسة تم تصميم استمارة استبيان بالمقابلة الشخصية حيث بلغ حجم العينة( 20) عشرين مربياً، وتم استخدام الجداول التكرارية والنسب المئوية في التحليل الإحصائي للبيانات. وقد أوضحت النتائج أن غالبية المبحوثين(70%) له زوجة واحدة، والغالبية العظمى من الإناث(90%) يعانين من الأمية، و(85%) من حالات الزواج من غير الأقارب، و(80%) يشركون نساءهم في اتخاذ القرارات المتعلقة بمعيشة الأسرة، في حين(90%) و(70%) منهم لا يشركونهن بالقرارات المتعلقة بتربية الإبل والقرارات المتعلقة بزواج الأبناء. كما أن غالبية المبحوثين(65%) يلجؤون إلى ممارسة طرق العلاج التقليدية، و(85%) لا يلجؤون إلى الوحدات البيطرية ولا يحصنون إبلهم ضد الأمراض. The study aimed to identify social and cultural characteristics of camel breeders in the Syrian Badia such as the social position, education, costumes of marriage and activities of women in that society. It also attempts to study their technical practices such as the formation of cattle, feeding and methods of controlling deceases. A questionnaire was administered to camel breeders. The total number of respondents was (20). The most important results of the study were as follows: about (70%) of the respondents married just one woman, most of the women were illiterate (90%). About (85%) of the respondents were married to relatives, about (80%) of the respondents shared decision-making with their wives, while most of them (65%) were using traditional methods to decease controlling and about (85%) of them did not treat with vaccine units.